Analisis Layanan ‘Wasit Vaksin’: Implementasi Agile Governance dalam Menghadapi Tantangan Krisis Kesehatan Global - Nabila Septia Rosa; Andra Pratama Juliyanto; Izzah Illiyyina (Public Sphere Review, 2026)
The Wasit Vaksin was present as a complaint service innovation with its effort to improve public services from Surabaya City Government to help community’s problem of COVID-19 vaccine certificate. The purpose of this research is to describe and analyze agile governance in the Wasit Vaksin complaint service and to identify its supporting and inhibiting factors. This research used a qualitative method with a descriptive approach. Data collection techniques were obtained through observation, interviews, and documentation, with informants determined by purposive and stratified random sampling. The data analysis technique used in this research refers to Miles and Huberman (2014), which includes data reduction, data display, and conclusion drawing/verification. The author conducted data analysis in accordance with the theory of agile governance proposed by Luna et al. (2015), focusing on four principles: human focused, based on quick wins, systematic & adaptive approach, and simple design & continuous refinement. The results show that the Surabaya City Government has not maximally implemented these four principles. This is because the application still requires updates, improved socialization programs for the community, and stronger coordination with the central government. The findings based on the agile governance perspective are expected to contribute to improving public services through digital technology, especially in responding to health crisis situations.